Pengembangan Media Pembelajaran Virtual Reality untuk Meningkatkan Keterampilan Menulis Teks Laporan Hasil Observasi pada Siswa SMP - Nurhayati, Nurhayati; Lubis, Lailan Syafira Putri; Kusyani, Diah; Harahap, Yunita Mutiara; Nurlela, Nurlela (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to develop and evaluate the feasibility of Virtual Reality (VR)-based instructional media to enhance studentsâ€™ writing skills in composing observational report texts at the junior secondary school level. The research is grounded in the observed deficiencies in students’ writing competence, which stem from limited access to real-life observational experiences and the prevalent use of conventional, non-contextual learning media. Employing a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), this study involved data collection through classroom observation, semi-structured interviews, questionnaires, and expert validation. The data were analyzed using both qualitative and quantitative methods. The findings indicate that the developed VR-based media is highly feasible, as evidenced by expert appraisals and positive feedback from both teachers and students. Furthermore, the results of quasi-experimental testing demonstrated a statistically significant improvement in studentsâ€™ writing performance. These findings suggest that integrating VR technology into Indonesian language instruction provides a more contextualized, interactive, and meaningful learning experience, thus fostering the achievement of educational goals in the digital era.